Answer:
a) v₁ = Lw / t - ½ gt , y = √ v₁² / 2g
b) y_total = Lw + √ (v₁² / 2g), v = √2 g y_total
Step-by-step explanation:
a) We can solve this exercise with the free fall equations
y = y₀ + v₁ t + ½ g t²
Point y₀ is the upper part of the window and point Lw the lower part, the velocity v₁ is the velocity at the top of the window
v₁ t = y - y₀ - ½ g t²
v₁ = (y-y₀) / t - ½ g t
v₁ = (Lw -0) / t - ½ g t
v₁ = Lw / t - ½ gt
This is the velocity at the top of the window
now let's work from the top of the window to where it came loose. At the point where the pot is released if speed is zero
v₁² = v₀² + 2g y
v₁² = 2 g y
y = √ v₁² / 2g
b) for ground speed
v² = v₀² + 2 g y_total
v = √2 g y_total
the height in this case is the height from where the pot was dropped
y_total = Lw + √ (v₁² / 2g)